Statistically Quantifying the Uncertainty in Strength of Marine Clay Stabilized by a Type of Portland-Fly Ash Cement - Zhi-Ren Zhu; Qiang-Qiang Cheng; Yang-Yang Chen; Elton J. Chen; Yuan Su (Advances in Civil Engineering)
This study deals with the variation in strength of clays stabilized by a special binder—the CEM II/B-V type of Portland-fly ash cement. Two sources of uncertainties were examined, that is, the uncertainty in cement fraction in the binder, and the nonuniformity in binder concentration resulted from the process of mixing binder slurry with in situ clays. These two uncertainties were quantitatively described as two random variables, and the analyses were conducted through the Monte Carlo simulation method. Results indicate that the strength is insensitive to the cement fraction in the binder but is sensitive to the binder concentration; the variation of the latter even results in an amplified variation of strength. The variation of binder concentration is proposed to be linked up with the variation of strength through the operational parameter of blade rotation number. By doing so, the results could benefit designers in quality control prior to the construction of soil stabilization.